IMPROVEMENT OF METHODOLOGICAL APPROACHES FOR THE APPLICATION OF ICONOGRAPHIC MATERIALS IN THE RESEARCH OF HISTORICAL PARKS - Gatalska, Nadiia (Theory and practice of design, 2023)
Purpose. Improving methodical approaches to the use of iconographic materials in the study of the transformation of landscapes of historical parks. Methodology. The basis for conducting research is the landscape-compositional approach, in which the landscape picture is considered as a fragment of the park environment and expands the properties of interconnected structures – graphic, volumetric-spatial, textured, textural and color. As the materials for the research, we used the iconographic materials from different periods of development of the State Dendrological Park “Alexandria”, as well as photos obtained as a result of own route surveys of the territory. Results. The article systematizes available scientific information on the study of the park compositional organization, including historical ones, provides their critical analysis, summarizes the complex of studies on the transformation of landscapes of the State Dendrological Park “Alexandria”, which allowed to deepen knowledge about the peculiarities of the use of iconographic materials in the study of historical parks. it pays special attention to the importance of individual elements of a landscape painting in the transformation of the landscape of the research object. Scientific news. The results of the analysis of the transformation of the landscapes of the State Dendrological Park “Alexandria” are presented, which became the basis for improving the methodical approaches of using iconographic materials in the study of historical parks. The algorithm of using iconographic materials of various stages of development of the historical park to determine the level of transformation of the composition of its landscape paintings is outlined. Practical significance. Methodical approaches to the use of iconographic materials in the study of historical parks have been improved, which can be used in pre-project searches in the development of project documentation for their adaptation.